Total Quality Management Tools: Are they Necessary for Improving Service Quality and Customer Satisfaction? - Alfalah, Tasneem F. (International Review of Management and Marketing, 2017)
Achieving service quality and customer satisfaction is necessary to obtain profitability and competitive advantage in any industry. Moreover, in any society, services are the core of economics, such as communications and transportation, and form the essential links among all sectors of the economy. However, the requests and needs of customers are continuously increasing, so that many social and technological improvements are needed, therefore it becomes apparent that the concept of service should be approached from a customer perspective. Many critical factors affect the development of TQM in service sector, one of these factors is TQM tools, and for service quality continues improvement. This research carried out an empirical study in the Jordanians 5 stars hotels to prove the importance of TQM tools in order to improve service quality and customer satisfaction. Keywords: TQM Tools, Service Quality, Customer Satisfaction, Five Stars Hotels, Jordan. JEL Classifications: L1, L8, M1